Studying the moments of encounter and (im)mobilities in artists' creative processes - Wingström, Roosa; Hautala, Johanna; Huopalainen, Astrid (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This article advances management and organization (MOS) research on the everyday creative process through an explorative study of artists. In this paper, we investigate moments of encounter-the coming together of different bodies and forces that create change in processes. We explore how encounters are enacted by various forms of mobility, such as geographical, corporeal, virtual, and imaginative mobility. Based on a two-week study including interviews, diaries, and mobility tracking, we analyze various encounters formed along (im)mobilities that drive the creative process by fostering stability, serendipitous engagements, and moments of stillness. This study extends the process theorization of creativity in MOS by highlighting encounters as drivers of the creative process. The encounters emerge through various forms of mobility. Mobility should thus be viewed as a crucial focus in both theoretical and empirical studies of creativity in MOS, as it deepens our understanding of creativity as a dynamic and contingent process.